Oxford Case Histories in Cardiology - Rajendram, Rajkumar ; Ehtisham, Javed and Forfar, Colin (Oxford, New York Oxford Univ Press, 2011)
A case-based guide for student directed learning aimed at specialist exams in cardiology and acute medicine in the UK and Europe
Include Index
Keywords: Heart--Diseases